Implementation of Registration of Transfer of Ownership Rights on the Basis of Grant in Semarang City - Ferdiansyah Marlinda, Herdyn (Jurnal Konstatering, 2026)
This study aims to determine and examine the implementation of the transfer of ownership rights based on grants in Semarang City, to determine and examine the obstacles and solutions in the process of registering the transfer of ownership rights based on grants in Semarang City, and to find out the deed of grant. The research approach method used in this thesis is a qualitative approach. The specifications of this study use descriptive analysis. The types of data used in this study are primary data including interviews with Land Office Officials or Employees and Land Deed Making Officials in Semarang City, as well as secondary data containing books and other supporting documents. Research data collection by interview. The data analysis method used in analyzing the data is descriptive qualitative. The results of the study indicate that the implementation of the transfer of ownership rights registration based on grants in Semarang City through 2 (two) stages namely making a deed of grant at the Land Deed Making Official (PPAT) and registering at the National Land Agency of Semarang City, as well as obstacles and solutions in the process of registering the transfer of ownership rights to land due to grants in Semarang City in the form of certainty of rights and issues regarding land registration fees.